Evaluation of Maize Covered Smut (Ustilago maydis) Management Options in Eastern Amhara, Ethiopia - Kassaw, Admasie; Desale, Tesfaye; Ayalew, Abebe; Abtie, Abate; Tiruneh, Abiye; Wudu, Eshete (Department of Agronomy and Horticulture, IPB University, 2025)
Maize, one of the most important cereal crops in the world, faces severe production constraints in Ethiopia due to covered smut disease. Field experiments were conducted at Sirinka and Cheffa during the 2022-2023 cropping seasons to evaluate management practices against maize covered smut. Seven treatments consist of five fungicides, cow urine, hot water, and untreated control, arranged in a randomized complete block design with three replications. The study found notable variations in disease intensity, maize grain yield, and yield components among the treatments. The application of proceed plus fungicide and the use of cow urine treatments were effective in reducing maize covered smut disease and higher yields of maize compared to other treatments and control plots. The combined analysis indicated that the highest maize grain yield (3120 and 2806 kg.ha-1) was recorded from carboxin + thiram + imidacloprid, and triadimefon fungicide-treated plots, followed by cow urine seed treatment (2649 kg.ha-1), while the lowest (1601 kg.ha-1) was recorded from untreated control plot. The highest net benefit (125310 ETB) was obtained from carboxin + thiram + imidacloprid, followed by Triadimefon (112986.8 ETB) and cow urine (107084.5 ETB) treated plots. Therefore, based on the partial economic analysis result, carboxin + thiram + imidacloprid fungicide and cow urine as a seed treatment are recommended for maize producers.